2013
DOI: 10.3329/bjmb.v6i1.13283
|View full text |Cite
|
Sign up to set email alerts
|

Renal function impairment in Hypothyroidism

Abstract: Background: Hypothyroidism is an important public health problem in Bangladesh. It is associated with increased risk for atherosclerosis and other complications. The frank development of hypothyroidism is associated with metabolic derangements including dyslipidemia- which is an etiopathologic factor for development of renal impairment. This study was to evaluate whether hypothyroidism is associated with impaired renal function. Methods: Using a cross sectional analytical study design, a total of 111 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…In the case of hypothyroidism, almost all the assessed electrolyte balance indicates a decrement; however the decrement is not statistically significant. This study finding was different from similar studies conducted by Chaudhury HS et al [ 22 ]. Decreased thyroid hormones, decreases the plasma rennin, angiotensin II, and serum angiotensin converting enzyme levels.…”
Section: Discussioncontrasting
confidence: 99%
“…In the case of hypothyroidism, almost all the assessed electrolyte balance indicates a decrement; however the decrement is not statistically significant. This study finding was different from similar studies conducted by Chaudhury HS et al [ 22 ]. Decreased thyroid hormones, decreases the plasma rennin, angiotensin II, and serum angiotensin converting enzyme levels.…”
Section: Discussioncontrasting
confidence: 99%
“…A study conducted by Chaudhury et al found that patients with hypothyroidism (the case group) had a higher BMI than those in the control group. This alteration in BMI could be a reflection of decreased basal metabolic rate and direct TSH stimulation of preadipocyte differentiation, resulting in adipogenesis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, similar result for serum creatinine has also reported. 6,7 Relatively comparable changes in serum creatinine with hypothyroidism have been accounted for in segregated contextual investigations and couple of different examinations having lesser number of hypothyroid patients. 8 Indeed, even newborn children with intrinsic hypothyroidism have demonstrated higher serum creatinine levels in the extent of the seriousness of hypothyroidism, however, no impacts were seen on serum urea levels.…”
Section: Discussionmentioning
confidence: 99%